Analyzing The Relationship Between Activity and Cognitive Achievement to Improve English Language Learning Ability (Case Study of PAUD Seruni) - Aprillia, Aprillia (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study aims to analyze the relationship between teacher activity and learning achievement so that there is an ability to increase early childhood English learning using talking englsih learning media, the subject of this research is PAUD Seruni Tangerang city with a total of 10 students consisting of 6 boys and 4 girls and 2 teaching teachers, Data collection methods are carried out through observation and assessment documentation. The results of the assessment that has been carried out through observation for 2 weeks obtained research data The first week of teacher activity shows that in the first observation 45% is still not good and the achievement of children's coginitive learning english language Starting to Develop (MB) 26-50, in the second observation week to teacher activity shows to be 77% very good and the achievement of children's coginitive learning english language and the achievement of children's coginitive learning english language (BSB) 76-100. The relationship between teacher activities and coginitive achievement is very influential to improve children's ability to recognize English words learning at PAUD Seruni Tangerang City.